HUBUNGAN LAMA KERJA, GERAKAN BERULANG DAN POSTUR JANGGAL TERHADAP KEJADIAN CARPAL TUNNEL SYNDROME (CTS) PADA PEKERJA TAHU BAKSO (Studi Kasus Pada Pekerja Tahu Bakso Kelurahan Langensari, Ungaran Barat) - Ella Wulandari; Baju Widjasena; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2020)
Carpal Tunnel Syndrome is a type of disorder that occurs due to pressure of the median nerve in the carpal tunnel on the wrist, which is characterized by symptoms of tingling, pain, numbness in the fingers and hands. Tofu meatballs workers are manual jobs that had a lot of repetitive motion for a long duration. The purpose of this study was to analyze the correlation of work duration, repetitive motion and odd postures with the occurrence of Carpal Tunnel Syndrome (CTS) towards tofu meatballs workers in Langensari Village, West Ungaran. This study used observational study using quantitative methods with cross sectional approach. The sample in this study was 27 of tofu meatballs workers who were selected based on the total sampling method. This study used questionnaire to see work duration and repetitive motion, nordic body map discomfort to see the risk of odd postures, Phalen's test to find out the occurrence of Carpal Tunnel Syndrome. Results of fisher exact test showed that there were correlation between work duration with the occurrence of CTS (p-value= 0.004), correlation between repetitive motion with the occurrence of CTS (pvalue= 0.006) and correlation between odd postures with the occurrence of CTS (pvalue= 0.046). The researcher suggest respondents to have stretching periodically before and after work.